FL 1060: a new beta-lactam antibiotic with novel properties - Greenwood, D. (1973)
The effect of FL 1060, a newly described beta-lactam antibiotic, on three strains of Escherichia coli was studied. The agent showed extraordinarily high activity as judged by conventional titrations, but inoculum size, osmolality of the medium, and length of the incubation period were all found to have a marked effect on the result. Continuous turbidimetric monitoring and microscopical observation of cultures of E. coli exposed to FL 1060 showed the effect of the antibiotic to have many novel features. Exposed bacterial rods converted to spherical forms, but in a different manner from that of classical penicillin-mediated transformation. Furthermore, although FL 1060 was bactericidal for the majority of the bacterial population, a fraction not only survived its lethal action but grew in high concentrations of the agent thereby producing a phenotypically resistant population which nonetheless continued to show characteristic morphological deformities. Possible reasons for this anomalous behaviour are discussed.